Effects of a Fragmented View of One’s Partner on Interpersonal Coordination in Dance - Brown, Derrick D.; Meulenbroek, Ruud G. J. (Frontiers in Psychology, 2016)
In this study we investigated the effects of a mirror-mediated, partial view of one’s dance partner on interpersonal coordination in dance duets. Fourteen participant pairs (dyads) were asked to perform a reflectionally-symmetric eight-segment dance-relevant arm movement sequence in two visual conditions: with one dancer facing the mirror and providing a partial view on the dance partner, or both dancers facing back to back with, for both dancers, no view on one’s partner. During an eight-count beat-preparation phase, the task was paced via a metronome at three TEMPI; 1.6, 1.9, and 2.3 Hz, which was subsequently removed after which the movement sequence continued in silence. Interpersonal coordination was assessed using two tri-axial wireless accelerometers, one fixed to each dancer, that allowed the off-line kinematic analyses of dyad correlation, mean relative phase and mean standard deviation of relative phase of the up–down movements of (one of) the hands of the two dancers. In addition, two independent raters estimated the realized movement frequencies and percentage of the trial duration that the dancers moved in sync. Repeated measure ANOVAs revealed systematic effects of tempo on the performance measures, a positive effect of the use of the mirror on the coordination of the dancers’ movements but no facilitating effect of the mirror on the dancers’ synchronization. Overall, the results support the contention that when dancing to an internalized rhythmic beat the use of a mirror provides an ecological means to stabilize interpersonal coordination in dance duets without an effect on synchronization.